SenseCam: A wearable Camera that Stimulates and Rehabilitates Autobiographical Memory - Hodges, S.; Berry, E.; Wood, K.; Woodberry, Ken; Hodges, Steve (Memory, 2011)
SenseCam is a wearable digital camera which captures an electronic record of the wearer’s day. It does this by automatically recording a series of still images through its wide-angle lens, and simultaneously capturing a log of data from a number of built-in electronic sensors. Subsequently reviewing a se-quence of images appears to provide a powerful autobiographical memory cue. A preliminary evaluation of SenseCam with a patient diagnosed with severe memory impairment was extremely positive; periodic review of images of events recorded by SenseCam resulted in significant recall of those events. Fol-lowing this, a great deal of work has been undertaken to explore this phenome-non and there are early indications that SenseCam technology may be beneficial to a variety of patients with physical and mental health problems and is valua-ble as a tool for investigating normal memory through behavioural and neu-roimaging means. Elsewhere, it is becoming clear that judicious use of SenseCam could significantly impact the study of human behaviour. Mean-while, research and development of the technology itself continues with the aim of providing robust hardware and software tools to meet the needs of clinicians, patients, carers and researchers. In this paper we describe the history of SenseCam, the design and operation of the SenseCam device and the associated viewing software, and we overview some of the ongoing research questions be-ing addressed with the help of SenseCam.